Relationship between workplace violence and mental/physical health of security guards during the COVID-19 pandemic in Taiwan - Lee, Ying-Han; Wu, Yun-Hsuan; Chen, Chiu-Ying; Chiao-Tzu Lee, Patricia; Lin, Tzu-Hsien; Lai, Chane-Yu (Frontiers in Public Health, 2024)
Objectives: To investigate the relationship between workplace violence (WPV) and mental and physical health (MPH) of security guards during the COVID-19 pandemic in Taiwan.A cross-sectional survey was conducted in 15 representative security companies across northern, central, and southern Taiwan, and outlying islands from July 2021 to June 2022 during the COVID-19 pandemic. 1200 questionnaires were distributed. A total of 1032 valid questionnaires were collected.Results: 13.18% of the participants reported that they had experienced WPV during the COVID-19 pandemic, including physical violence (PhV), psychological violence (PsV), verbal violence (VV), and sexual harassment (SH). The most common violence was VV (54.19%), followed by PsV (20.69%). Community residents and property owners were the primary perpetrators, followed by strangers. The study showed that the security guards who had experienced WPV had higher scores on the 12-item Chinese Health Questionnaire (Taiwan version) (CHQ-12), indicating poorer MPH than those who had never experienced WPV. The result showed that VV had strong correlations with the lack of effective communication, dissatisfaction with treatment and service attitude, and work stress. PsV was strongly associated with excessive waiting times.Conclusions: There were correlations among PhV, VV, and PsV and they had adverse impacts on MPH, except for SH. The study found that the primary perpetrators of WPV against security guards were community residents and property owners. The causes were the lack of effective communication, dissatisfaction with treatment and service attitude, excessive waiting times, and work stress, which further led to turnover intention and poor MPH. The findings of this study have useful implications and it is recommended to enhance the understanding of workplace violence against security guards and to formulate appropriate local and international strategies to address it.